Dance, sports or academics: which monopolize students emotional quotient - George, Neethu; D., Rock Britto; George, Meera; Venkataramani, Samanvita; M., Kavya; S., Aswitha Priya M.; Roy, Ronald (International Journal of Research in Medical Sciences, 2018)
Background: Emotional Intelligence (EI), often measured as an Emotional Intelligence Quotient (EQ), refers to skills that provide the ability to balance emotions and reason, which provides long-term happiness. Focus on Intelligence Quotient (IQ) in the current era has to be changed for the betterment of society. Objectives was to assess and compare Emotional Quotient (EQ) among students who excel in dance, sports, and academics. Methods: This was a cross-sectional study conducted among three groups of minimum 30 students who are excellent in dance, academics or sports. EQ was assessed using a 22 item EQ test which measures the psychological dimensions such as emotional sensitivity, emotional maturity and emotional competency and also total EQ. Results: Out of 91 students, maximum students were having extremely high EQ in the domains of emotional sensitivity 36 (39.6%), emotional competency 88 (96.7%) and total EQ 85 (93.4%). Dancers showed significantly high EQ in the domains of emotional maturity, emotional competency, and overall EQ compared to sportspersons and academicians. Increased age, agriculture and business occupation of mother and presence of another sibling were significantly associated with emotional intelligence of students. Conclusions: This study showed that inclusion of extracurricular activities like dance and sports along with academics may improve the self-confidence and increased awareness about one’s own emotions, leading to raised EQ.